Mussel-inspired human gelatin nanocoating for creating biologically adhesive surfaces - Yang X (Dove Medical Press, 2014)
Xi Yang,1,2 Liping Zhu,1 Seiichi Tada,1 Di Zhou,3 Takashi Kitajima,1 Takashi Isoshima,1 Yasuhiro Yoshida,1,4 Mariko Nakamura,1,5 Weiqun Yan,2 Yoshihiro Ito1,3 1Nano Medical Engineering Laboratory, RIKEN, Saitama, Japan; 2School of Pharmaceutical Sciences, Jilin University, Jilin, People’s Republic of China; 3Emergent Bioengineering Materials Research Team, RIKEN Center for Emergent Matter Science, Saitama, 4Department of Biomaterials and Bioengineering, Graduate School of Dental Medicine, Hokkaido University, Hokkaido, 5Dental Hygiene Program, Kibi International College, Okayama, Japan Abstract: Recombinant human gelatin was conjugated with dopamine using carbodiimide as a surface modifier. This dopamine-coupled human gelatin (D-rhG) was characterized by 1H-nuclear magnetic resonance, mass spectroscopy, and circular dichroism. D-rhG-coated surface properties were analyzed by physicochemical methods. Additionally, cell attachment and growth on the modified surfaces was assessed using human umbilical endothelial cells. Binding of gelatin onto titanium was significantly enhanced by dopamine conjugation. The thickness of the D-rhG coating depended on the treatment pH; thicker layers were formed at higher pH values, with a maximum thickness of 30 nm. D-rhG enhanced the binding of collagen-binding vascular endothelial growth factor and cell adhesion as compared with gelatin alone, even at the same surface concentration. The D-rhG surface modifier enhanced substrate binding by creating an adhesive nanointerface that increased specific protein binding and cell attachment. Keywords: recombinant human gelatin, dopamine, natural catechols, cell adhesion, cell culture, titanium